Technical Aspects of Dealing with Difficult Laparoscopic Cholecystectomy in Overweight and Obese Patients - Fawad, Muhammad; Razzaque, Hasnain; Akram, Sohail; Imran, Muhammad; Rashid, Fahad; Sufyan, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Laparoscopic cholecystectomy (LC) is the preferred surgical approach for gallstone disease; however, obesity presents unique technical challenges, including prolonged operative time, increased conversion rates, and higher postoperative complications. Limited data exist regarding the impact of obesity on LC outcomes in the Pakistani population, necessitating further investigation. Objective: This study aimed to evaluate the technical difficulties, intraoperative modifications, and perioperative outcomes of LC in overweight and obese patients compared to normal-weight individuals, with a focus on operative time, conversion rates, and postoperative complications. Methods: A quasi-experimental study was conducted at the Department of Surgery, CMH Rawalpindi, from September 2022 to April 2023, involving 300 patients categorized by BMI into normal weight (n=100), overweight (n=120), and obese (n=80). Inclusion criteria encompassed adults undergoing LC for symptomatic cholelithiasis or acute cholecystitis, while exclusions included patients with severe systemic illnesses or prior upper abdominal surgeries. Data on intraoperative challenges, operative time, conversion to open surgery, and postoperative complications were analyzed using SPSS v27. Statistical significance was set at p<0.05. Results: Obese patients had significantly longer operative times (75 ± 20 min) than normal-weight individuals (60 ± 15 min) (p<0.01). Conversion rates were highest in obese patients (10%) compared to normal-weight (2%) (p<0.05). Postoperative complications, including wound infections (10% vs. 2%) and bile leaks (3.8% vs. 1%), were significantly more common in obese individuals (p<0.05). Conclusion: Obesity complicates LC, leading to longer operative times, higher conversion rates, and increased postoperative morbidity. Surgical modifications and perioperative strategies should be tailored to mitigate these risks, ensuring optimal outcomes for obese patients.